2016
DOI: 10.1136/bcr-2016-216057
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal tuberculosis: an old disease surprising young doctors

Abstract: Tuberculosis remains a worldwide public health concern. Atypical extrapulmonary presentations may delay the diagnosis and treatment. We present the case of an adult woman admitted to the emergency department with bowel obstruction. The putative intraoperative diagnostic hypothesis was ovarian cancer with peritoneal dissemination. Histopathological analysis showed a chronic granulomatous inflammatory disease with acid-fast bacilli. The patient was started on an alternative parenteral antituberculosis drug combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We report the case that has peritoneal dissemination expressed as multiple enlarged lymph nodes within the cavity. Coincidentally, Sousa MD reported that tuberculosis bore a striking resemblance to malignancy so that a hypothesis of cancer with peritoneal dissemination had been accepted before histopathological analysis showed a tubercular disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…We report the case that has peritoneal dissemination expressed as multiple enlarged lymph nodes within the cavity. Coincidentally, Sousa MD reported that tuberculosis bore a striking resemblance to malignancy so that a hypothesis of cancer with peritoneal dissemination had been accepted before histopathological analysis showed a tubercular disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis can distribute widely to organ system of the body resulting in extrapulmonary tuberculosis represented for about 14% of tuberculosis cases worldwide in 2017 [2]. Extrapulmonary tuberculosis that manifest as abdominal tuberculosis is only 1-3 % of all tuberculosis cases worldwide but untreated abdominal tuberculosis carries significant mortality rate of 60% [3], [4]. There are few reports in the literature describe prevalence of colonic tuberculosis, nevertheless Indonesia is country with third highest tuberculosis burden [5].…”
Section: Introductionmentioning
confidence: 99%